How Creative Economy Development Plays a Role as a Driving Force in Community-Based Tourism Village Development? An Empirical Study in Central Java Province - Oktavilia, Shanty; ., Firmansyah; ., Suharno; ., Fafurida; Rahman, Yozi Aulia; Adzim, Fauzul (Journal of Ecohumanism, 2024)
This study aims to develop a Creative Economy Development Strategy as a Driving Force for Community-Based Tourism Village Development. This study uses quantitative and qualitative approaches. This study uses primary and secondary data. Data collection methods in this study include observation, interviews, documentation, and questionnaires. The questionnaire in this study was addressed to key persons consisting of several elements including academics, government, society, NGOs, Communities, and also the private sector. The results of this study indicate that Infrastructure and Accessibility and Policy and Regulatory Support have the highest weights, which means that supporting factors such as infrastructure and government policies are very important in the development of creative economy-based tourism villages. Policy and Regulatory Support and Local Human Resource Empowerment are the next priority criteria. Provision of Grants and Subsidies for Creative MSMEs has the highest final score, which means that these elements are alternative strategies that are the main priority for driving the creative economy. Improving Road Connectivity to Villages, Training in Crafts, Fine Arts, and Local Culinary, and Adding Tourism Support Facilities are important strategies to increase the attractiveness and accessibility of tourism villages. The development of galleries or showrooms for MSME products and digital campaigns through social media are also considered strategic in supporting the promotion of local creative products.